Optimalisasi Sistem Informasi Keuangan Daerah di Indonesia: Pendekatan Evaluasi CIPP terhadap Asimetri Kapasitas Institusional - Alfascadieno Akbar Fatoni (Research and Development Agency Ministry of Home Affairs, 2026)
Regional financial management in Indonesia necessitates comprehensive transparency, accountability, and integration, driven by the mandate to implement the Regional Government Information System (SIPD). Although the policy architecture has been established nationally, its execution at the provincial level indicates significant asymmetric disparities. This study evaluates the implementation and administration of regional finances through the SIPD platform in three provinces—West Java, Banten, and Jambi—which represent high, moderate, and low-performance clusters, respectively. Employing a descriptive qualitative approach predicated on the Context, Input, Process, Product (CIPP) evaluation model, data were collected through in-depth interviews, participant observation, and document analysis. The findings indicate that the aggregate implementation of SIPD has not yet achieved an optimal level. Contextually, the policy is highly congruent with the regional urgency for a single data architecture. However, the input evaluation reveals a severe gap regarding human resource competencies and digital infrastructure. The process evaluation highlights crucial technical impediments, encompassing shadow manual procedures, double-entry bookkeeping practices, and Application Programming Interface (API) synchronization failures, particularly in Banten and Jambi, whereas West Java demonstrates precise alignment between planning and budgeting. The product evaluation illustrates an uneven distribution of benefits; West Java achieved profound transparency with efficient disbursements, while Jambi and Banten continue to struggle with administrative inconsistencies. Central government interventions via technical guidance and iterative system updates have mitigated several constraints but necessitate more targeted intensification. This study concludes that the standardization of business processes, enhancement of technical infrastructure, and sustainable development of human capital are strategic imperatives for optimizing SIPD and actualizing accountable regional financial governance.